Murderous Violence at Work: conflict and aggression in Indian auto factories. (1st April 2015) - Santanu Sarkar
Abstract : Considerable scholarly attention has been paid to the growing incidence of workplace violence and homicide in India. In seeking to understand the cause of this workplace mayhem, most commentators regard employer repression as playing an important role. This article revisits four recent episodes of workplace homicide and analyses the anecdotal information available in the public domain on these cases, using a multi-level analytical framework. It argues that these incidents can best be understood within a perspective that takes into account not only factors in the specific workplace environment in the context of neoliberal low road employment policies but also the broader social-economic environment of a developing country where rapid industrialisation and migration are taking place in newly urbanised sites characterised by sharp social and economic polarisation.